1999
DOI: 10.1017/s0025315499001460
|View full text |Cite
|
Sign up to set email alerts
|

Age and growth of the echinoid Sphaerechinus granularis from the Algerian coast

Abstract: The growth bands in the plates of the echinoid Spharechinus granularis settled on the Algerian coast were analysed. Two distinct groups of sea urchins were identified with different growth patterns related to the period of recruitment, i.e. spring or autumn. The growth rate of the autumn cohort was higher over the year following the first winter after settlement. From the second winter there was little growth difference between the two cohorts. Compared to populations from Atlantic sites, the Algerian populati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 4 publications
0
4
1
Order By: Relevance
“…In effect the densities obtained were in average lower that those reported by Alves et al (2001) who already referred average densities lower than 2 ± 0.6 ind./m 2 . The present results were much lower than those reported for the northwestern (< 30 ind./m 2 to < 2 ind./m 2 in Marseille Bay-Sartoretto and Francour, 1997) and for the southwestern (1.4-4.9 ind./m 2 in Algeria- Soualili et al, 1999) Mediterranean coast. Both studies indicated that the species density was affected by sea urchin size, depth, and season, with higher densities found during summer and autumn in shallower grounds and composed by relatively small animals (diameter < 58 mm) (Sartoretto and Francour, 1997).…”
Section: Discussioncontrasting
confidence: 87%
See 2 more Smart Citations
“…In effect the densities obtained were in average lower that those reported by Alves et al (2001) who already referred average densities lower than 2 ± 0.6 ind./m 2 . The present results were much lower than those reported for the northwestern (< 30 ind./m 2 to < 2 ind./m 2 in Marseille Bay-Sartoretto and Francour, 1997) and for the southwestern (1.4-4.9 ind./m 2 in Algeria- Soualili et al, 1999) Mediterranean coast. Both studies indicated that the species density was affected by sea urchin size, depth, and season, with higher densities found during summer and autumn in shallower grounds and composed by relatively small animals (diameter < 58 mm) (Sartoretto and Francour, 1997).…”
Section: Discussioncontrasting
confidence: 87%
“…The species is commonly found in the Mediterranean (Vafidis et al, 2020) and in the northeast Atlantic between the English Channel and the Gulf of Guinea (Guillou and Michel, 1993), including Madeira and other archipelagos of the Macaronesia biogeographic region (Alves et al, 2001;Riera et al, 2012;Madeira et al, 2019). Sphaerechinus granularis populations are characterized by low densities, although it can occur locally in high densities (e.g., in southern Brittany - Michel, 1993, western Mediterranean -Sartoretto andFrancour, 1997 and in the Bay of Algiers (Algeria) - Soualili et al, 1999). The species can be found from the intertidal zone to depths up to 130 m (Guillou and Michel, 1993), in both calm and exposed areas (Martínez-Pita et al, 2008) and is frequently associated with rhodoliths beds (aggregations of free-living coralline algae that cover extensive benthic areas of subtidal environments worldwide) (Guillou et al, 2002), although it may occur in sandy bottoms (Gaspar et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sphaerechinus granularis is a very common sea urchin inhabiting various sublittoral habitats and following specific depth-distributional patterns in different geographic sectors according to local environmental conditions [ 7 ]. In horizontally oriented mixed soft bottoms—consisting of seagrass meadows, muddy sands, and scattered boulders covered by various algal species, as the study area—the species thrives around 10 m. In the Mediterranean Sea, according to the very few relevant studies conducted for S. granularis , its density ranges from 1.8 to 315 individuals/100 m −2 in the NW (Spain) and SW (Algeria) sectors, respectively [ 9 , 23 ]. In the Aegean Sea, an overall density of 4.8 individuals/100 m −2 has been reported -a value very close to the one reported in the present study (5.0 individuals/100 m −2 )—which, however, varied greatly between geographic sectors, being much lower in the oligotrophic southern part [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although some species has been identified as good candidates for future commercial extraction [ 16 , 17 , 18 , 19 , 20 ] little is known about their biology, population dynamics, abundances and reproduction or growth rate due to their low commercial interest until now. In addition, these species can be found near or within P. lividus exploitation areas and might, therefore, be impacted by the activity of the fishery.…”
Section: Introductionmentioning
confidence: 99%